Sikap tentang aborsi pada siswi kelas XI - Laila, Farikhah Nur; Widyastuti, Yani; Widyasih, Hesty (Jurnal Kesehatan Ibu dan Anak, 2015)
Teenage pregnancy is closely related to unwanted pregnancy. The number of teenage pregnancies has increased based on SDKI 2007 to 2012. The aspects that need to be highlighted as a result of the end of unwanted pregnancy one is abortion. In Indonesia the abortion cases increase in 2012 with eight people died. From the data of SKRRI in 2007 on Indonesian teenagers and their permissive attitude toward abortion, the highest percentage is those women who are still in school (37.5%). This study is aimed to determine the description on abortion of the students in class XI at SMAN 11 Yogyakarta in 2015. This study is descriptive method with cross-sectional design. There are 156 respondents. The data measured are attitudes about abortion using questionnaire. The data analysis is performed using univariate. The result shows as many as 82 students (52.6%) of grade XI have positive attitude about abortion. Meanwhile, those having negative attitude are 74 respondents (47.4%). Those having positive attitude are the ones majoring in science, residing in urban areas, obtaining dominant sources of reproductive health information fromparents and having at least 3 sources of reproductive health information. Themajority students of class XI have positive attitude about abortion.